Vesicostomy as a Protector of Upper Urinary Tract in Long-Term Follow-Up - Prudente, Alessandro; Reis, Leonardo Oliveira; Franca, Rodrigo de Paula; Miranda, Marcio; D’ancona, Carlos Arturo Levi (Urology Journal, 2009)
Introduction: The aim of this study was to analyze the results of vesicostomy in children as a protector of the upper urinary tract and assess the adjustments taken by the caregivers. Materials and Methods: Twenty-one children who had undergone vesicostomy with the Blocksom technique were evaluated. Their mean age was 3.7 years (range, < 1 to 10 years). The evaluation consisted of kidney function tests, cystography, and analysis of complications. Twenty parents or caregivers were interviewed about their attitudes towards vesicostomy and its outcomes. Results: The main causes of the vesical dysfunction were posterior urethral valve in 7 (33.3%) and myelomeningocele in 5 patients (23.8%). Ten children (58.8%) showed improvement and 7 (41,2%) showed cure. Hydronephrosis observed in 17 children was alleviated or cured following the procedure. Kidney function, tested by creatinine clearance calculation, remained stable or improved in 20 patients (95.2%). Episodes of urinary tract infection and vesicoureteral reflux lowered in 8 of 21 (38.1%) and 10 of 14 patients (71.4%), respectively. Subjective evaluation of 20 cases showed that 18 children (90.0%) remained dry during the day and 14 caregivers/parents (70.0%) felt they had acquired the skills necessary to handle a patient with vesicostomy. The mean global rate of satisfaction of the results of the surgery ranging from 0 (worst result) to 10 (best result) was 8.7. Conclusion: Vesicostomy is a simple surgery that protects the upper urinary tract, decreases hydronephrosis, and improves kidney function. There was adequate adjustment to vesicostomy and a positive global evaluation as reported by the parents and caregivers.